Analisis Faktor Kualitas Produk Yang Menentukan Kepuasan Konsumen - Tombak Gapura Bhagya (Ekonam: Jurnal Ekonomi, Akuntansi & Manajemen, 2021)
Business competition in the service sector and in the manufacturing industry is very tight. The intense competition between these industries causes each industry to try to provide the maximum possible service and product quality. Therefore we need a study that discusses the factors of product quality that determine customer satisfaction. Where this research aims to determine what factors are dominant in product quality, to know how much consumer expectations and customer satisfaction on MT KPBS Pangalengan. This type of research uses descriptive method with sampling technique in the form of convenience sampling with a sample of 98 people. Continued using factor analysis to determine the dominant factor of product quality and using importance performance analysis to measure the level of customer satisfaction. Based on the research results, obtained 5 dominant factors of product quality, namely performance, service, features, suitability and durability. Meanwhile, the level of customer satisfaction is quite good because it turns out that the existing performance is above the average consumer's expectation. Although there is one factor that is still slightly below expectations, namely conformity with a satisfaction score of 97%.